Neural basis of functional fixedness during creative idea generation: An EEG study. (September 2018) - Camarda, Anaëlle; Salvia, Émilie; Vidal, Julie; Weil, Benoit; Poirel, Nicolas; Houdé, Olivier; Borst, Grégoire; Cassotti, Mathieu
Abstract: Decades of problem solving and creativity research have converged to show that the ability to generate new and useful ideas can be blocked or impeded by intuitive biases leading to mental fixations. The present study aimed at investigating the neural bases of the processes involved in overcoming fixation effects during creative idea generation. Using the AU task adapted for EEG recording, we examined whether participant's ability to provide original ideas was related to alpha power changes in both the frontal and temporo-parietal regions. Critically, for half of the presented objects, the classical use of the object was primed orally, and a picture of the classical use was presented visually to increase functional fixedness (Fixation Priming condition). For the other half, only the name of the object and a picture of the object was provided to the participants (control condition). As expected, priming the classical use of an object before the generation of creative alternative uses of the object impeded participants' performances in terms of remoteness. In the control condition, while the frontal alpha synchronization was maintained across all successive time windows in participants with high remoteness scores, the frontal alpha synchronization decreased in participants with low remoteness scores. In the Fixation Priming condition, in which functional fixedness was maximal, both participants with high and low remoteness scores maintained frontal alpha synchronization throughout the period preceding their answer. Whereas participants with high remoteness scores maintained alpha synchronization in the temporo-parietal regions throughout the creative idea generation period, participants with low remoteness scores displayed alpha desynchronization in the same regions during this period. We speculate that individuals with high remoteness scores might generate more creative ideas than individuals with low remoteness scores because they rely more on internal semantic association and selection processes. Highlights: We investigated the neural bases of the processes involved in overcoming a fixation. We used a new version of the AU task adapted for EEG recording. Priming the classical use of an object impeded creative performances. Creativity was related to alpha power changes in frontal and parietal regions.